The Use of Fuzzy Logic in Corporate Innovative Potential Assessment - Tomasz L. Nawrocki (Ekonometria)
The paper aims to present an empirical application of an originally developed model for corporate potential innovativeness assessment and comparison. The proposed model provides a framework for combined static and dynamic potential innovativeness assessment with the use of fuzzy logic. Fuzzy logic is used to assess corporate potential innovativeness from two perspectives: resources conditioning innovation activities in an enterprise, and the engagement of an enterprise in their continuous development. In this context, selected companies from the information technology sector listed on the Warsaw Stock Exchange were examined. The need for corporate innovativeness measurement and evaluation for management purposes arises from its growing importance in building enterprise value and achieving long-term competitive advantage. The proposed model enables the fairly current and good orientation in both general and a more in-depth innovativeness potential level of the assessed enterprises. This can be the basis for various comparison analysis and managerial decisions regarding e.g. innovation management as well as managing corporate image and reputation.(original abstract)